Design and implementation of a crossflow turbine for Pico hydropower electricity generation - C.H. Achebe; O.C. Okafor; E.N. Obika (Heliyon, 2020)
This study covered the design, implementation and performance evaluation of a crossflow turbine at various nozzle positions. The chosen blade material was analyzed using ANSYS for stress and deformation degree under the impact of hydraulic jets to ascertain its suitability while in operation. The shaft was analyzed under static and dynamic conditions using ANSYS in order to ensure a non-plastic deformation of the shaft at both conditions. The outcome of this analysis was employed in the harmonic response analysis of the runner shaft. Convergent tests were done for both the blade and runner shaft analysis. An experiment was designed for the evaluation of the crossflow turbine performance using optimal (custom) design tool of response surface methodology and 69 simulations/runs were obtained. The factors considered in the experimental design are: nozzle distance from the shaft, nozzle height and attack angle. The crossflow turbine was constructed using computed design values for all the machine's parts. The runner blades were positioned specifically at 28° outer blade angle and 90° inner blade angle. The turbine was tested under a water head and flow rate of 6.4m and 0.0042m3/s respectively. The shaft power and efficiency were evaluated using their respective formula. The responses were optimized in order to get the optimum position of the nozzle that would give the best performance of the responses using the two factor interaction (2F1) mathematical models in coded factors, developed for each of the response. The results obtained, proved that low carbon steel material was suitable for the turbine blading and the shaft is safe at both static and dynamic conditions since the induced stresses and deformations never exceeded the permissible range. Also, each of these considered nozzle positions had a significant effect on the responses with the nozzle height and attack angle having a combined effect on the performance of the turbine. The best turbine performance was obtained at lower angle of attack, nozzle distance very close to the runner shaft and at a nozzle height that will actualize greater energy impartation to the upper and lower blade profiles. The developed mathematical models for each response has higher correlation value, suggesting that the models are suitable for predicting the responses at the considered factor levels. An optimal nozzle distance, height and attack angle of 102mm, 413mm and 5° respectively, were obtained. At this nozzle position, the alternator gave an output of 35watts and 6V. When two voltage transformers were employed, it gave 200Volts AC. The turbine can be commercialized on large scale for greater output power using the determined optimal nozzle positions.